Empowering Workforce Skills through BLKK: A Community Service Initiative for Industry 4.0 - Masykur; Ahmad Syafiq; Khairil Anam; Gian Nova Sudrajat Nur (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: This study addresses the critical issue of workforce readiness for Industry 4.0, focusing on the community service subject of the Balai Latihan Kerja Komunitas (BLKK) vocational training program. It aims to evaluate the program's effectiveness in enhancing the skills of participants from rural and underserved communities to meet modern labor market demands. Purpose of the Study: The purpose is to assess the impact of the BLKK program on improving participants' employability and entrepreneurial preparedness. Its objectives are to evaluate training effectiveness, measure participant satisfaction and self-efficacy gains, and identify key factors for sustainable skill development. Methods: The research employed a Participatory Action Research (PAR) approach, actively engaging at least 34 BLKK partners and participants in identifying skill gaps and co-creating the training curriculum. The analysis was framed within a multidisciplinary theoretical framework combining Empowerment Theory, Human Capital Theory, and Digital Literacy Theory. Results: The findings indicate exceptionally high participant satisfaction, with a mean score of 4.38/5 for training quality. The program successfully enhanced economic preparedness, with 59% of participants strongly agreeing they felt more prepared for employment or entrepreneurship. Key to this success was the integration of digital literacy, technical skills, and continuous mentoring. Recommendations include expanding digital literacy components and strengthening long-term mentorship and external network support to ensure program sustainability and economic inclusion.